Implementasi Sistem Pemilihan Pembina PPNPN dengan Menggunakan Metode Profile Matching : (Studi Kasus Balai Laboratorium Bea dan Cukai Medan) (International Forum of Researchers and Lecturers, 2024)
The process of directly appointing supervisors for non-state civil servant government employees (PPNPN) at the Medan Customs and Excise Laboratory (BLBC) creates obstacles, due to the absence of a comprehensive assessment such as the social and managerial competence of prospective mentors. This research aims to increase the accuracy of selecting PPNPN supervisors using the profile matching method. This method compares individual competency with position competency to find the gap value between the two. There are 10 alternative names that will be analyzed in this research. The results of this research are a ranking of the names. The alternative that gets the highest ranking is the one who has the right to become the PPNPN supervisor. From the results of the profile matching method calculations that have been carried out, it is found that the employee candidate who has the right to become the selected PPNPN supervisor is Eka Soraya Siregar with a score of 4.18.